Synthesis of well-defined catechol polymers for surface functionalization of magnetic nanoparticles. Issue 45 (2nd November 2016) - Zhang, Qiang; Nurumbetov, Gabit; Simula, Alexandre; Zhu, Chongyu; Li, Muxiu; Wilson, Paul; Kempe, Kristian; Yang, Bin; Tao, Lei; Haddleton, David M.
Abstract : Well-defined fluorescent functional polymers with terminal catechol groups were synthesized by SET-LRP under aqueous conditions for " grafting to " modification of iron oxide nanoparticles. Abstract : In order to obtain dual-modal fluorescent magnetic nanoparticles, well-defined fluorescent functional polymers with terminal catechol groups were synthesized by single electron transfer living radical polymerization (SET-LRP) under aqueous conditions for " grafting to " modification of iron oxide nanoparticles. Acrylamide, N -isopropylacrylamide, poly(ethylene glycol) methyl ether acrylate, 2-hydroxyethyl acrylate, glycomonomer and rhodamine B piperazine acrylamide were homo-polymerized or block-copolymerized directly from an unprotected dopamine-functionalized initiator in an ice-water bath. The Cu-LRP tolerated the presence of catechol groups leading to polymers with narrow molecular weight distributions ( M w / M n < 1.2) and high or full conversion obtained in a few minutes. Subsequent immobilization of dopamine-terminal copolymers on an iron oxide surface were successful as demonstrated by Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), transition electron microscopy (TEM) and thermogravimetric analysis (TGA), generating stable polymer-coated fluorescent magnetic nanoparticles. The nanoparticles coated with hydrophilic polymers showed no significant cytotoxicity when compared with unmodified particles and the cellular-uptake of fluorescent nanoparticles by A549 cells was very efficient, which also indicated the potential application of these advanced nano materials for bio-imaging.